2010
DOI: 10.1620/tjem.222.311
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Scanning Reveals Complex Etiology of Oculo-Auriculo-Vertebral Spectrum

Abstract: Oculo-auriculo-vertebral spectrum (OAVS) is a common developmental disorder involving first and second pharyngeal arches. Although some family cases and such patients showing chromosomal aberrations suggest that OAVS have a genetic basis, no consistent genetic defects have been recorded at present time. Thus, we conducted genetic studies of a three-generation family with five OAVS patients to identify a causative variant for OAVS. Cytogenetic studies revealed those family members had a normal karyotype and no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 37 publications
2
22
0
Order By: Relevance
“…13 Th is reinforces the hypothesis that genetic heterogeneity and a variety of pathogenic mechanisms are contributory causes of this clinical entity, including epigenetic inheritance. 16 According to some authors, the VACTERL association and OAVS are a spectrum of anomalies derived from mesenchymal structures, probably caused by the same pathogenic mechanism.…”
Section: Discussionsupporting
confidence: 72%
“…13 Th is reinforces the hypothesis that genetic heterogeneity and a variety of pathogenic mechanisms are contributory causes of this clinical entity, including epigenetic inheritance. 16 According to some authors, the VACTERL association and OAVS are a spectrum of anomalies derived from mesenchymal structures, probably caused by the same pathogenic mechanism.…”
Section: Discussionsupporting
confidence: 72%
“…We also propose that the phenotype is affected by other genetic and non-genetic factors, in line with a oligogenic or even a multifactorial etiology [18]. It is seems clear to us that there are other genetic loci involved in OAVS and using a genome-wide exome or whole genome sequencing approach would be important to identify the gene(s) involved in its etiology.…”
Section: Accepted Manuscriptmentioning
confidence: 90%
“…Moreover, clinical studies have shown that, following careful history and clinical examination of the relatives of probands with OAVS, up to 45% of "unaffected" relatives do have minor OAVS manifestations [13]. Reports of familial cases following Mendelian inheritance [4,[14][15][16][17], as well as evidence for genetic linkage in two families [18,19], and the presence of OAVS features in patients with various chromosomal aberrations and genomic imbalances [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38], all suggest that some cases of OAVS have a genetic basis. Environmental causes have also been suggested, particularly twinning, assisted reproductive techniques and maternal pre-pregnancy diabetes [1,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although concordance has been reported for both monozygotic and dizygotic twins, the high level of discordance in monozygotic twins suggests that both genetic and environmental factors are involved [11,[17][18][19][20][21][22][23] . Currently, there is no specific causing gene that can be tested [24] .…”
Section: Discussionmentioning
confidence: 99%